Structural characterization of hexameric shell proteins from two types of choline‐utilization bacterial microcompartments. Issue 9 (2nd September 2021) - Ochoa, Jessica M.; Mijares, Oscar; Acosta, Andrea A.; Escoto, Xavier; Leon-Rivera, Nancy; Marshall, Joanna D.; Sawaya, Michael R.; Yeates, Todd O.
Abstract : Several crystal structures are analyzed of proteins that form the shells of bacterial microcompartment organelles. These new structures are from microcompartments where the metabolic substrate choline diffuses across the shell‐protein pore. Abstract : Bacterial microcompartments are large supramolecular structures comprising an outer proteinaceous shell that encapsulates various enzymes in order to optimize metabolic processes. The outer shells of bacterial microcompartments are made of several thousand protein subunits, generally forming hexameric building blocks based on the canonical bacterial microcompartment (BMC) domain. Among the diverse metabolic types of bacterial microcompartments, the structures of those that use glycyl radical enzymes to metabolize choline have not been adequately characterized. Here, six structures of hexameric shell proteins from type I and type II choline‐utilization microcompartments are reported. Sequence and structure analysis reveals electrostatic surface properties that are shared between the four types of shell proteins described here.